2004
DOI: 10.4049/jimmunol.172.12.7510
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Peptide Inhibitor of Janus Kinase 2 That Mimics Suppressor of Cytokine Signaling 1 Function

Abstract: Positive and negative regulation of cytokines such as IFN-γ are key to normal homeostatic function. Negative regulation of IFN-γ in cells occurs via proteins called suppressors of cytokine signaling (SOCS)1 and -3. SOCS-1 inhibits IFN-γ function by binding to the autophosphorylation site of the tyrosine kinase Janus kinase (JAK)2. We have developed a short 12-mer peptide, WLVFFVIFYFFR, that binds to the autophosphorylation site of JAK2, resulting in inhibition of its autophosphorylation as well as its phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
101
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 36 publications
7
101
0
Order By: Relevance
“…Intracellular delivery of Tkip via a lipophilic (N-terminal palmitylated) derivative inhibited IFNg antiviral activity and IFNg-mediated induction of MHC Class I (Flowers et al, 2004). It was also demonstrated that Tkip inhibits the autophosphorylation of EGFR by an unknown mechanism using in vitro kinase assays.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…Intracellular delivery of Tkip via a lipophilic (N-terminal palmitylated) derivative inhibited IFNg antiviral activity and IFNg-mediated induction of MHC Class I (Flowers et al, 2004). It was also demonstrated that Tkip inhibits the autophosphorylation of EGFR by an unknown mechanism using in vitro kinase assays.…”
mentioning
confidence: 94%
“…We previously developed a short 12-mer peptide mimetic of SOCS-1, WLVFFVIFYFFR (Tkip), that binds to the autophosphorylation site of JAK2, resulting in inhibition of its autophosphorylation as well as its phosphorylation of gamma interferon (IFNg) receptor subunit IFNGR-1 (Flowers et al, 2004). Intracellular delivery of Tkip via a lipophilic (N-terminal palmitylated) derivative inhibited IFNg antiviral activity and IFNg-mediated induction of MHC Class I (Flowers et al, 2004).…”
mentioning
confidence: 99%
See 3 more Smart Citations